Reorienting Locus of Control in Individuals Who Have Offended Through Strengths-Based Interventions: Personal Agency and the Good Lives Model - Tyler, Nichola; Heffernan, Roxanne; Fortune, Clare-Ann (Frontiers in Psychology, 2020)
Having an external locus of control has been associated with a range of well supported risk correlates of offending behaviour. Further, individuals with an internal locus of control orientation are suggested to be more open to engaging in treatment and are also considered more likely to have successful treatment outcomes. In forensic settings, where individuals are subject to external controls and have little personal autonomy, it is important to consider what treatment approaches might be most successful in reorienting individuals’ locus of control. The Good Lives Model (GLM) proposes a strengths-based approach to the rehabilitation of individuals who have offended. Within the GLM, an external locus of control is suggested to be associated with a deficit in the primary good of agency. In this article we will provide a brief overview of the literature on locus of control and its hypothesized role in offending behavior. We will discuss how an external locus of control orientation is related to personal agency and how strengths-based models, such as the GLM, may assist with reorienting locus of control in individuals who have offended through promoting personal agency.